Visual science and engineering models and applications - Kelly, D. H. (Dondald H.) (Optical engineering, 1994)
This work examines a broad spectrum of the latest topics in visual science, relating basic studies to applications and delineating points of intersection among the various disciplines that study the mechanisms of vision. It discusses, among other topics: the Purkinje-image eyetracker; the principles of high-definition television; and the role of stabilized-image technology in revealing how eye movements control both luminous and chromatic perceptions.